Does Mild Hydronephrosis Induced by Full-Bladder Improve Outcomes in Patients Undergoing Shock Wave Lithotripsy for Lower Calyceal Stones?: A Prospective Randomized Study - Hazar, Ismet Ayd?n; Cakiroglu, Basri; Sinanoglu, Orhun; Akgün, Feride Sinem; Arda, Ersan; Yuksel, Ilkan; Akdere, Hakan (Urology Journal, 2018)
Purpose: To compare the outcomes, sessions and shock wave numbers in patients undergoing standard procedure shock wave lithotripsy (SWL) and patients undergoing SWL with mild hydronephrosis induced by full-bladder following oral hydration before SWL procedure for lower calyceal stones. Materials and Methods: Between January 2014- January 2016 a total of 371 patients who underwent SWL, for lower pole calyceal stones ? 2 cm, were included into the study. 127 patients were treated in the supine position (Group A), 123 in the prone position (Group B) and 121 in the prone position with full bladder and mild hydronephrosis checked by ultrasound before procedure (Group C). There were 286 men and 85 women with a mean ± SD age of 36 ± 11 years Results: The mean (SD) stone sizes within the group A, group B and group C were 11 mm (±3 mm), 12 mm (±4.1 mm) and 11 mm (± 3.8 mm) respectively. No significant difference was found in age (P = .18) and stone size between 3 groups (P = .07). The median interquartile range (IQR) number of shocks within the group A, group B and group C were 7600 (3855), 6500 (4300) and 6700 (4915) respectively. Significant difference was found in number of shock waves among 3 groups (P < .01). The difference between groups according to stone expulsion rate was found significant in all sessions (P = .01). Conclusion: The present study suggests that mild hydronephrotic status induced by full-bladder before SWL can lower cost and patient discomfort by decrease in number of sessions and increase in stone clearance.